Characteristics and outcomes of sepsis patients with and without COVID-19 - Lars Heubner; Sara Hattenhauer; Andreas Güldner; Paul Leon Petrick; Martin Rößler; Jochen Schmitt; Ralph Schneider; Hanns Christoph Held; Jan Mehrholz; Ulf Bodechtel; Maximilian Ragaller; Thea Koch; et al. (Elsevier, 2022)
Background: The aim of this study was to describe and compare clinical characteristics and outcomes in critically ill septic patients with and without COVID-19. Methods: From February 2020 to March 2021, patients from surgical and medical ICUs at the University Hospital Dresden were screened for sepsis. Patient characteristics and outcomes were assessed descriptively. Patient survival was analyzed using the Kaplan-Meier estimator. Associations between in-hospital mortality and risk factors were modeled using robust Poisson regression, which facilitates derivation of adjusted relative risks. Results: In 177 ICU patients treated for sepsis, COVID-19 was diagnosed and compared to 191 septic ICU patients without COVID-19. Age and sex did not differ significantly between sepsis patients with and without COVID-19, but SOFA score at ICU admission was significantly higher in septic COVID-19 patients. In-hospital mortality was significantly higher in COVID-19 patients with 59% compared to 29% in Non-COVID patients. Statistical analysis resulted in an adjusted relative risk for in-hospital mortality of 1.74 (95%-CI=1.35-2-24) in the presence of COVID-19 compared to other septic patients. Age, procalcitonin maximum value over 2 ng/ml, need for renal replacement therapy, need for invasive ventilation and septic shock were identified as additional risk factors for in-hospital mortality. Conclusion: COVID-19 was identified as independent risk factor for higher in-hospital mortality in sepsis patients. The need for invasive ventilation and renal replacement therapy as well as the presence of septic shock and higher PCT should be considered to identify high-risk patients.